TYPES OF MODERN PEDAGOGICAL TECHNOLOGIES - Ibragimova Gulnora Xavazmatovna (Web of Journals Publishing, 2025)
This article provides an overview of various modern pedagogical technologies that are transforming the landscape of education. It categorizes these technologies into distinct types, including blended learning, flipped classrooms, gamification, project-based learning, personalized learning, collaborative learning, and adaptive learning. Each type is examined in terms of its characteristics, benefits, and impact on student engagement and learning outcomes. By integrating digital tools and innovative instructional strategies, these technologies promote active participation, critical thinking, and personalized learning experiences. The article highlights how the adoption of modern pedagogical technologies enhances educational practices, prepares students for the challenges of the 21st century, and fosters a more inclusive and effective learning environment.
Keywords: Modern pedagogical technologies, Blended learning, Flipped classroom, Gamification, Project-based learning, Personalized learning, Collaborative learning, Adaptive learning, Student engagement, Active learning, Digital tools, Educational innovation, Teaching strategies, Learning outcomes, 21st-century skills.